Protocol for the EARCO Registry: a pan-European observational study in patients with α1-antitrypsin deficiency. Issue 1 (2nd March 2020) - Greulich, Timm; Altraja, Alan; Barrecheguren, Miriam; Bals, Robert; Chlumsky, Jan; Chorostowska-Wynimko, Joanna; Clarenbach, Christian; Corda, Luciano; Corsico, Angelo Guido; Ferrarotti, Ilaria; Esquinas, Cristina; Gouder, Caroline; et al.
Rationale and objectives: Alpha-1 antitrypsin deficiency (AATD) is a genetic condition that leads to an increased risk of emphysema and liver disease. Despite extensive investigation, there remain unanswered questions concerning the natural history, pathophysiology, genetics and the prognosis of the lung disease in association with AATD. The European Alpha-1 Clinical Research Collaboration (EARCO) is designed to bring together researchers from European countries and to create a standardised database for the follow-up of patients with AATD. Study design and population: The EARCO Registry is a non-interventional, multicentre, pan-European, longitudinal observational cohort study enrolling patients with AATD. Data will be collected prospectively without interference/modification of patient's management by the study team. The major inclusion criterion is diagnosed severe AATD, defined by an AAT serum level <11 µM (50 mg·dL −1 ) and/or a proteinase inhibitor genotype ZZ, SZ or compound heterozygotes or homozygotes of other rare deficient variants. Assessments at baseline and during the yearly follow-up visits include lung function testing (spirometry, body plethysmography and diffusing capacity of the lung), exercise capacity, blood tests and questionnaires (symptoms, quality of life and physical activity). To ensure correct data collection, there will be designated investigator staff to document the data in the case report form. All data will be reviewed by the EARCO database manager. Summary: The EARCO Registry aims to understand the natural history and prognosis of AATD better with the goal to create and validate prognostic tools to support medical decision-making. The EARCO Registry is a non-interventional, multicentre, pan-European, longitudinal observational cohort study enrolling patients with AATD to elucidate the natural history, pathophysiology, genetics and prognosis of this condition http://bit.ly/369ScCc